IT Governance as Drivers of Dynamic Capabilities to Gain Corporate Performance Under the Effects of Environmental Dynamism - Yoshikuni, Adilson Carlos (International Journal of Business, Economics and Management, 2021)
For researchers and practitioners, there is an important central question to answer, how information technology (IT) governance can help organizations survive and thrive in constantly changing business environments. To address this issue, this study examines the influence of IT governance on dynamic capabilities to sustain corporate performance under environmental dynamism. Tests of the proposed model were performed using survey data from 147 Brazilian firms to support the hypotheses. The results demonstrated that IT governance is a core enabler of dynamic capabilities innovation and operational capabilities for corporate performance gains. The heterogeneity tests also showed that the firm’s orientation strategy of prospector and analyzer, under conditions of high dynamism environmental, increased the value of IT governance to enable innovation capability, while the impact of IT governance-enabled operational capabilities under low dynamism, amplified the firm’s orientation strategy of defender and reactor. For practical application, this study indicated that managers should be knowledgeable about how IT governance capability plays a fundamental role to enable dynamic capabilities and generate economic payoffs.